2018
DOI: 10.1177/1049732318784815
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Self-Monitoring in Self-Directed Weight Loss and Weight Loss Maintenance: Systematic Review of Qualitative Studies

Abstract: The experience and role of self-monitoring in self-directed weight loss attempts may be distinctly different from that within formal interventions, and has yet to be fully explored. We systematically reviewed qualitative studies to examine experiences of self-monitoring as an aid to self-directed weight loss. Thematic synthesis was used to construct descriptive and analytical themes from the available data. In all, 22 studies (681 participants) were included, in which the uses of self-monitoring ranged from an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…Interalia, this has potential implications on data interpretation that we have identified as a recurring concept across studies. Previous research demonstrated the importance of PGHD interpretation and its wider implications [46], with missing sense-making skills and the fear of self-interpretation mentioned as key challenges to personal health information use. Our findings reflected that importance, as a major proportion of the literature directly or indirectly addressed interpretability by describing various approaches to fostering correct data understanding.…”
Section: Discussionmentioning
confidence: 99%
“…Interalia, this has potential implications on data interpretation that we have identified as a recurring concept across studies. Previous research demonstrated the importance of PGHD interpretation and its wider implications [46], with missing sense-making skills and the fear of self-interpretation mentioned as key challenges to personal health information use. Our findings reflected that importance, as a major proportion of the literature directly or indirectly addressed interpretability by describing various approaches to fostering correct data understanding.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, adherence to self‐monitoring of weight was lower than that of eating or physical activity. There may be unique challenges for self‐monitoring of weight that need to be addressed clinically, such as a sense of shame regarding one's weight (regardless of recent progress) or avoidance that results when one fears that recent weight change will be disappointing . However, it is difficult to interpret the decline in adherence to weight self‐monitoring because the prescription for frequency of weight self‐monitoring changed from weekly to daily during the final weeks of the programme, and thus, the change in frequency prescribed is confounded with the timing of the initial weight loss phase of treatment coming to an end.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a review of just-in-time interventions suggested that portable devices may be useful to enhance cognitive behavioral therapy for weight loss programs [12]. Mobile phones also provide an avenue for regular self-monitoring, which have been strongly linked with successful behavior change, particularly in weight management [13,14].…”
Section: Introductionmentioning
confidence: 99%